2017
DOI: 10.5194/acp-17-12659-2017
|View full text |Cite
|
Sign up to set email alerts
|

A new balance formula to estimate new particle formation rate: reevaluating the effect of coagulation scavenging

Abstract: Abstract.A new balance formula to estimate new particle formation rate is proposed. It is derived from the aerosol general dynamic equation in the discrete form and then converted into an approximately continuous form for analyzing data from new particle formation (NPF) field campaigns. The new formula corrects the underestimation of the coagulation scavenging effect that occurred in the previously used formulae. It also clarifies the criteria for determining the upper size bound in measured aerosol size distr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…Their occurrence frequency and, more importantly, their contribution to particle number concentrations were found to be substantial or determinant in the global troposphere (Spracklen et al, 2006;Kulmala et al, 2014). Moreover, their contribution to the number of cloud condensation nuclei (CCN) can be 50 % or even more (Makkonen et al, 2009;Merikanto et al, 2009;Sihto et al, 2011), which links the events to the climate system and emphasizes their global relevance Makkonen et al, 2012;Carslaw et al, 2013;. New particle formation and growth events were proved to be common in polluted air of large cities as well, with a typical relative occurrence frequency between 10 % and 30 % (Woo et al, 2001;Baltensperger et al, 2002;Alam et al, 2003;Wehner et al, 2004;Salma et al, 2011;Dall'Osto et al, 2013;Xiao et al, 2015;Zhang et al, 2015;Kulmala et al, 2017, Nieminen et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Their occurrence frequency and, more importantly, their contribution to particle number concentrations were found to be substantial or determinant in the global troposphere (Spracklen et al, 2006;Kulmala et al, 2014). Moreover, their contribution to the number of cloud condensation nuclei (CCN) can be 50 % or even more (Makkonen et al, 2009;Merikanto et al, 2009;Sihto et al, 2011), which links the events to the climate system and emphasizes their global relevance Makkonen et al, 2012;Carslaw et al, 2013;. New particle formation and growth events were proved to be common in polluted air of large cities as well, with a typical relative occurrence frequency between 10 % and 30 % (Woo et al, 2001;Baltensperger et al, 2002;Alam et al, 2003;Wehner et al, 2004;Salma et al, 2011;Dall'Osto et al, 2013;Xiao et al, 2015;Zhang et al, 2015;Kulmala et al, 2017, Nieminen et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric measurements have shown that the presence of dicarboxylic acids, including succinic acid (SUA), is prevalent in ambient particles (Kawamura and Kaplan, 1987;Decesari et al, 2000;Legrand et al, 2005;Hsieh et al, 2007;Blower et al, 2013). The effect of dicarboxylic acids on aerosol nucleation involving SA or base molecules has been recognized in theoretical studies.…”
Section: Introductionmentioning
confidence: 99%
“…), natural sources (wildfires, volcanoes, deserts, etc. ), and chemical processing of gases and aerosol (Robinson et al, 2007;Zhang et al, 2007;Jimenez et al, 2009;Calvo et al, 2013). However, traffic (Zhu et al, 2002;Charron and Harrison, 2003;Fruin et al, 2008;Wehner et al, 2009), cooking (Saha et al, 2019;Abernethy et al, 2013), and new particle formation (Brines et al, 2015;Hofman et al, 2016) are generally considered the only major sources of urban UFPs.…”
mentioning
confidence: 99%